2017
DOI: 10.1038/srep43357
|View full text |Cite
|
Sign up to set email alerts
|

The enhanced photo absorption and carrier transportation of InGaN/GaN Quantum Wells for photodiode detector applications

Abstract: We have conducted a series of measurements of resonantly excited photoluminescence, photocurrent and photovoltage on InGaN/GaN quantum wells with and without a p-n junction under reverse bias condition. The results indicate that most of the resonantly excited photo-generated carriers are extracted from the quantum wells when a p-n junction exists, and the photon absorption of quantum wells is enhanced by the p-n junction. Additionally, the carrier extraction becomes more distinct under a reverse bias. Our find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…Stacking faults are two-dimensional defects which exist because of a partial displacement that affects the regular lattice stacking sequence. In wz III-nitrides, stacking faults that lie along the basal (0001) planes are basal stacking faults while those that lie along the prismatic planes such as (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are prismatic stacking faults.…”
Section: Structural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Stacking faults are two-dimensional defects which exist because of a partial displacement that affects the regular lattice stacking sequence. In wz III-nitrides, stacking faults that lie along the basal (0001) planes are basal stacking faults while those that lie along the prismatic planes such as (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) are prismatic stacking faults.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…Importantly, by replacing traditional lighting sources, the power-saving nature of InGaN-based white LEDs can not only reduce global carbon emissions, helping to fight climate change, but can also allow people in remote areas access to ambient lighting [12,13]. Apart from LEDs, InGaN has also been crucial in the advancement of other optoelectronic technology including laser diodes (LDs), photovoltaics and photodetectors [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…So MQWs is hard to be used in light-toelectric devices due to the low escape rate. But relevant experiments demonstrated an obvious carriers escape phenomenon in PIN structure (an intrinsic layer sandwiched in the p-type and n-type layer) with MQWs [10][11][12][13][14][15], where the carriers break the quantum confinement and the escape proportion can be up to 90 percent, which is too high to be explained by thermal-electron emission and tunneling theory [5,19,20]. These results implies that the MQWs in PIN structure could be used in light-to-electric devices, such as solar cells [16,17] and photodetectors [10,18].…”
Section: Introductionmentioning
confidence: 99%
“…al. reported that p-i-n InGaN/GaN MQW LEDs that behave like photodiodes (PDs) under light illumination due to presence of an electrical field at the pn junction facilitates the extraction of photogenerated carriers from MQWs [13]. With the monolithic p-i-n PD and LED, a warning system has been proposed for UV light detection [14].…”
Section: Introductionmentioning
confidence: 99%